2012
DOI: 10.1038/modpathol.2011.208
|View full text |Cite
|
Sign up to set email alerts
|

Clinical assessment of PTEN loss in endometrial carcinoma: immunohistochemistry outperforms gene sequencing

Abstract: PTEN is a tumor suppressor that negatively regulates the PI3K-AKT signaling pathway, which is implicated in the pathogenesis of endometrial carcinoma. Sanger sequencing has been considered to be the gold standard for detection of PTEN sequence abnormalities. However, this approach fails to address the epigenetic mechanisms that contribute to functional PTEN loss. Using a study cohort of 154 endometrioid and non-endometrioid endometrial carcinomas, we performed full-length PTEN sequencing and PTEN immunohistoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
108
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(115 citation statements)
references
References 42 publications
6
108
1
Order By: Relevance
“…The staining frequency of individual markers in our study is consistent with previous studies. [6][7][8]11,[16][17][18][19][20][21][22] By analyzing marker combinations using nominal logistic regression models and restricting the analysis to cases with an unambiguous morphological diagnosis (submitted consensus diagnosis), we identified a seven-marker panel (ER, CDKN2A (p16), TP53, VIM, PTEN, PGR, and IGF2BP3) that could differentiate endometrioid carcinoma FIGO grade 3 from serous carcinoma with 100% concordance compared with the morphological gold standard. Interestingly, a similar approach to the subclassification of high-grade endometrial carcinomas using mutational profiles did not generate a reliable multivariate logistic regression model.…”
Section: Modern Pathology (2013) 26 1594-1604mentioning
confidence: 99%
See 2 more Smart Citations
“…The staining frequency of individual markers in our study is consistent with previous studies. [6][7][8]11,[16][17][18][19][20][21][22] By analyzing marker combinations using nominal logistic regression models and restricting the analysis to cases with an unambiguous morphological diagnosis (submitted consensus diagnosis), we identified a seven-marker panel (ER, CDKN2A (p16), TP53, VIM, PTEN, PGR, and IGF2BP3) that could differentiate endometrioid carcinoma FIGO grade 3 from serous carcinoma with 100% concordance compared with the morphological gold standard. Interestingly, a similar approach to the subclassification of high-grade endometrial carcinomas using mutational profiles did not generate a reliable multivariate logistic regression model.…”
Section: Modern Pathology (2013) 26 1594-1604mentioning
confidence: 99%
“…It has also been shown that certain immunohistochemical markers such as PTEN 'outperform gene sequencing'. 22 Nevertheless, it is prudent to study how mutational status and immunohistochemical profiles overlap with each other and with morphology. Potentially, the best markers that arise from both techniques could be used as an ancillary technique to morphology to subclassify high-grade endometrial carcinomas in the future.…”
Section: Modern Pathology (2013) 26 1594-1604mentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemical loss of PTEN included specimens scored as negative and heterogeneous according to previous reported methods. 38,39 Statistical Analysis Kruskal-Wallis test was used to compare the RQ of miRNA expression with respect to pathological findings of patients. Pathologic diagnosis was used as a standard reference.…”
Section: Immunohistochemical Analysis Of Pten Loss Of Expressionmentioning
confidence: 99%
“…The deregulation of multiple elements of the mTOR pathway, such as amplification or mutation of PI3K, loss of PTEN function, and overexpression of AKT, S6K1, 4EBP1, and eIF4E, has been reported in numerous types of human diseases, including cancer, cardiac hypertrophy, type 2 diabetes, and obesity. (8,12,14). Aberrations of the mTOR signaling pathway are common in several types of human cancers, such as breast, ovarian, prostate, bladder, thyroid, colon, and head and neck cancers (8,(15)(16)(17)(18).…”
mentioning
confidence: 99%